THE INTERVENTION WITH JUVENILE OFFENDERS: ITS DEVELOPMENT IN SPAIN - Coy Ferrer, Ernesto; Torrente, Ginesa (Anales de Psicología / Annals of Psychology)
This work aims at offering a general view of how the intervention with the juvenile offender has developed in Spain. Basic characteristics of the Tutelary Model are analized, being this model the starting point for the 1948 juvenile Courts Act. This Act, which is based on the Model of Justice, has been in force in Spain until the enactment of the current Act on June 5th 1992. The work also sets out in detail every possible measure to be adopted concerning juvenile justice: admonishment, supervisory, non-custodial sentences, fostering, depriving the juvenile of his right to drive, community service orders, and finally, open, semi-open or closed prision. The out-of-court agreements are proposed as an alternative and finally, the article offers a brief review of the current legislative trends concerning the juvenile in Spain.